Delapan Kunci Sukses Strategi Penerapan Teknologi Informasi Pada Perusahaan Menufaktur - Prayitno, Agus (JURNAL PENELITIAN EKONOMI DAN BISNIS, 2011)
The purpose of this study is to describe the steps of strategy of information technology (IT) that has been done be large companies in Central Java and found the key of success implementation of IT strategy. Respondents in this study were 126 leaders that responsible for assessing the management of information technology. Using a confirmatory analysis of variable IT strategy concluded that there are eight keys strategy to optimize the success of IT Implementation are : the company needs to prepare a framework of IT strategies exploring the external of IT, identify internal IT, has a program of IT implementation, have the budget of IT, has a service area of IT, IT manager has the same level with other business managers, There are communication executives of IT with other executives.Kata kunci : Strategi teknologi informasi.